2023
DOI: 10.1108/ijbpa-02-2023-0015
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable management of heritage buildings in long-term perspective (SyMBoL): current knowledge and further research needs

Chiara Bertolin,
Filippo Berto

Abstract: PurposeThis article introduces the Special Issue on Sustainable Management of Heritage Buildings in long-term perspective.Design/methodology/approachIt starts by reviewing the gaps in knowledge and practice which led to the creation and implementation of the research project SyMBoL—Sustainable Management of Heritage Buildings in long-term perspective funded by the Norwegian Research Council over the 2018–2022 period. The SyMBoL project is the motivation at the base of this special issue.FindingsThe editorial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…The interaction between the three keywords and the twenty-two UNESCO TIs, among which the 'conservation' keyword assumes the highest values (Figure 5 and Table 3) and occurs specifically for both TI n. 2 'Sustainable management of heritage' and TI n. 14 CK (values = 717, 2075), such findings support Bertolin and Berto, who call for the need for more research to evaluate the associated risks and digital preservation of sustainable energy management in a Norwegian context [78]. The third value = 636 is present on TI n. 22 'Participatory processes'.…”
Section: Mapping the Abstract With Tis Ats And CCsupporting
confidence: 64%
“…The interaction between the three keywords and the twenty-two UNESCO TIs, among which the 'conservation' keyword assumes the highest values (Figure 5 and Table 3) and occurs specifically for both TI n. 2 'Sustainable management of heritage' and TI n. 14 CK (values = 717, 2075), such findings support Bertolin and Berto, who call for the need for more research to evaluate the associated risks and digital preservation of sustainable energy management in a Norwegian context [78]. The third value = 636 is present on TI n. 22 'Participatory processes'.…”
Section: Mapping the Abstract With Tis Ats And CCsupporting
confidence: 64%
“…Risk associated with maintenance stage need to be mitigated. Maintenance is pertinent in the life of a building, especially heritage and historic buildings (Bertolin and Berto, 2024). They found that the construction stage has the highest risk occurrences, followed by the tendering stage.…”
Section: Risk Management Practices In a Developing Countrymentioning
confidence: 99%